Historical Dimensions of the 9/11 Attacks in America - Dhobi, Saleem (Historical Journal, 2024)
The causes of the September eleven attacks on the World Trade Center and the Pentagon—the financial and military powers of the United States of America respectively—have been manifold. The inquiry into the historical veracities demonstrates that political, cultural and ideological have been the primary foundations of the conflict between the Americans and the perpetrators of the horrific incidents that took lives of many and left uncountable number of people traumatized. This paper investigates into the potential causes of the tragedy based on the secondary data from different scholarly writings of the post-9/11 attacks. The findings exhibit whatever the reasons have been of the attacks is traumatic and can trigger the clash between Western and Islamic civilizations at any momentum. Since the origin of divergence between the Western countries and the Middle Eastern nations lies in the political history that draws the line between these two civilizations which have collided against each other at different phases. The 9/11 attacks on the icons of American economy and militarism have not taken place in vacuum. Rather there have been diverse factors that led both Osama bin Laden—the commander-in-chief of Al-Qaeda and the Americans in general and the mainstream Americans in particular. The tragedy was the apex of their clash as perceived in the history of human civilization.